54.0k views
3 votes
Please help me!!!!!!!

Please help me!!!!!!!-example-1
User Dauffret
by
4.6k points

1 Answer

4 votes

9514 1404 393

Answer:

A) (-6, 8)

B) (x, y) ⇒ (-x, y)

Explanation:

B) The rule for reflection across the y-axis is that the x-coordinate changes sign:

(x, y) ⇒ (-x, y)

__

A) To find the pre-image point, one can simply reflect the image back across the y-axis:

A'(6, 8) ⇒ A(-6, 8)

User George Phillipson
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.